Euphoria : a novel - King, Lily (New York : Atlantic Monthly Press, 2014)
English anthropologist Andrew Bankson has been alone in the field for several years, studying the Kiona river tribe in the territory of New Guinea. Haunted by the memory of his brothers' deaths and increasingly frustrated and isolated by his research, Bankson is on the verge of suicide when a chance encounter with colleagues, the controversial Nell Stone and her wry and mercurial Australian husband Fen, pulls him back from the brink.
Map on lining papers.
Maine author.
Keywords: Anthropologists -- New Guinea -- Fiction; Nineteen thirties -- Fiction; Married people -- Fiction; Man-woman relationships -- Fiction; Triangles (Interpersonal relations) -- Fiction; New Guinea -- Fiction